A Unique Four-Point Approach for Removal of Giant Breast Fibroadenoma With Marked Asymmetry: A Modified Round Block Technique. Issue 8 (13th September 2020) - Cui, Haidong; Liu, Jian; Guo, Jufeng; Hu, Shufang; Xiang, Aizhai; Ma, Shenglin
Abstract: Purpose: The removal of the giant breast fibroadenoma (GFA) with esthetic repair of the severe deformed breast is a surgical challenge. Materials and Methods: This was a retrospective study of data of 10 patients with GFAs who treated with a modified round block technique at the Department of Breast Surgery, Hangzhou First People's Hospital (Hangzhou, Zhejiang province, China) from March 2014 to June 2017. Preoperatively, according to the degree of excess skin and asymmetry, a four-point approach was designed. The area between the inner and outer circles was de-epidermized. The tumors were entirely stripped off along the capsule through an incision on a part of the outer circle. To avoid the nipple–areola complex widening, purse-string suture technique was used. Results: Patients' age ranged from 12 to 32 years (mean age, 23 years), and the largest tumor weighed 2 kg, with a diameter of 16.5 cm. After a mean follow-up of 25 months (range, 9–32 months), no local recurrences were found. Cosmetic results were satisfactory with breast symmetry and minimal scarring. Complications were minimal and widening of the periareolar scar was slight as well. Conclusion: The modified round block technique is recommended to resect GFA in order to improve the cosmetic results with minimal scar.